1991
DOI: 10.1115/1.2912807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Linear Profile Modification and Loading Conditions on The Dynamic Tooth Load and Stress of High-Contact-Ratio Spur Gears

Abstract: This paper presents a computer simulation for the dynamic response of high-contact-ratio spur gear transmissions. High contact ratio gears have the potential to produce lower dynamic tooth loads and minimum root stress but they can be sensitive to tooth profile errors. The analysis presented in this paper examines various profile modifications under realistic loading conditions. The effect of these modifications on the dynamic load (force) between mating gear teeth and the dynamic root stress is presented. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…The problem is then reduced to finding the relief amplitude Ẽ * minimising (11): Combining (7), (11) and (12) leads to the following equation:…”
Section: Global Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is then reduced to finding the relief amplitude Ẽ * minimising (11): Combining (7), (11) and (12) leads to the following equation:…”
Section: Global Approximationmentioning
confidence: 99%
“…Since tooth correction amplitudes depend on deflections, profile and lead modifications are usually calibrated for one specific design load whereas, in a number of applications, load can vary substantially. Numerous contributions are available in the literature showing the applications of tooth profile modifications to spur and helical gears with both low and high contact ratios [7][8][9][10][11][12][13][14][15][16][17][18]. However, most of the recent results are based on intensive numerical simulations which, if very accurate, do not necessarily lend themselves to a complete understanding of the effects of design parameters and operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on [4], [8], , , [11] and [13], performance diagrams can be established as shown in Figure 5 which, for all low-contact ratio gear geometries, illustrate the design criterion evolutions when changing profile relief amongst the set of modifications along the master curve in Figure 2. It is observed, in particular, that the design criteria can be classified in two families: a) the maximum contact pressure and root stress which are reduced when longer optimum relief is used and, b) the loss factor and contact length reduction (or actual contact ratio) which increase as longer relief is considered.…”
Section: Performance Diagrams On the Master Curvementioning
confidence: 99%
“…who found that they were influential on off-lineof-action contacts and could strongly reduce the vibration and noise of spur gears at one particular load, coined 'design load' (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In this context, approximate design rules for profile relief in spur gears have been established (9-10), (12) whereas, for helical gear teeth, the definition of modifications mostly relies on extensive numerical simulations (11), (13)(14)(15)(16)(17) from which general trends can hardly be extrapolated.…”
mentioning
confidence: 99%
See 1 more Smart Citation